A dinamização econômica nos territórios Açu-Mossoró e sertão do Apodi (RN): um estudo na cadeia produtiva da apicultura e sua gestão nas unidades de produção familiar - Rocha, Rosimary da Silva (Universidade Federal Rural do Semi-Árido, 2015)
This study aimed to analyze the productive chain of apiculture and its economic dynamization in Açu-Mossoro and Backland of Apodi territories in the State of Rio Grande do Norte. It was used a theoretical construction that involved the steps in all a process of the family farming and its integration in agroindustry and the consolidation of the productive chain of honey. In the method of the collect data of the research was made beyond of a census that includes all organizations that work with honey in the yar of 2011 represented by an apiarist in the local where work (co-operative, warehouse, associations or honey house) therefore, it was a study that used the comparative method of the apiculture chains in the two territories. This step was of fundamental importance for the investigation that had as support the application of a questionnaire for an audience of 63 key informants of each organization, counting as an analytical basis of variable used, it adopting procedures quantitative and qualitative. The study of the productive chain of apiculture in territories of Açu-Mossoró and Backland of Apodi made it possible the accompaniment of this activity with the purpose to know the mains barriers and challenges of the culture of the systemic form the allowed search solutions for raise the quality of the product in the decision making, commercialization and formulation of public policies. The research data prove that some institutions supported the apiarists, however their implemented actions, beyond of credits or technical assistance, still suffers of some problems as absence of measures of an assessment system and accompaniment in the sense of the organization from the production, involved all the infrastructure and prioritizing the quality of products, to get the products certification that still show to be a big obstacle for the commercialization. With the analysis in the sense to deepen the knowledge and with a schematic survey of apiculture, it can formulate important conclusions depicting apiarian activity in the two territories, including to detect that the infrastructure analyzed was one of the main causes of the difficulties for certification and commercialization, too, approached aspects social, economics, technological and environmental that allowed identify weakness and optimization of the activity, for to can direct relevant decisions in the agribusiness and that consequently stimulate the rulers to develop public policies directed to this kind of producer
Keywords: Apicultura; Instituições; Infraestrutura; Certificação e Políticas Públicas; Apiculture; Institutions; Infrastructure; Certification and Public Policies; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE